2011
DOI: 10.1002/cphc.201100854
|View full text |Cite
|
Sign up to set email alerts
|

Transient Grating Studies of Femtosecond Processes in Ultra‐Thin Layers of PTCDA

Abstract: Elementary processes like energy transfer, charge transport, and exciton diffusion in thin films occur on time scales of femtoseconds. Time-resolved photo-electron spectroscopy, a technique limited to ultra-high vacuum environment and the proper choice of a substrate, has been used to study ultrafast processes in sub-nanometer thin films so far. Herein we show that a transient (population) grating created by the interference of laser pulses can be used to study ultrafast processes in such films under ambient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This implementation of the generalized LIA is suited to analyze the phase and amplitude of the noisy signals in optical non-linear spectroscopy. [10][11][12][13] The generalized LIA uses a comb-pass filter. This means it selects not only a single Fourier component of the signal at the frequency ω sig but all the other components at ω sig + ω 0 , ω sig + 2ω 0 , ... etc.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…This implementation of the generalized LIA is suited to analyze the phase and amplitude of the noisy signals in optical non-linear spectroscopy. [10][11][12][13] The generalized LIA uses a comb-pass filter. This means it selects not only a single Fourier component of the signal at the frequency ω sig but all the other components at ω sig + ω 0 , ω sig + 2ω 0 , ... etc.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…They demonstrated that the observation of how lateral carrier diffusion affects the exciton dynamics is possible because of the increased spatial resolution. In our own work, we have studied very thin layers of an organic semiconductor and have also investigated dynamics using SNOM in combination with different nonlinear spectroscopy techniques. , …”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our previous works, ,, the work presented in the following combines scanning near-field optical microscopy with femtosecond time-resolved pump–probe spectroscopy (PP-SNOM) to study concurrent charge pair dynamics at the Au–P3HT interfaces, thereby revealing the elementary quenching process localized at the metal surface.…”
Section: Introductionmentioning
confidence: 99%